Systematic Analysis of Intestinal MicroRNAs Expression in HCC: Identification of Suitable Reference Genes in Fecal Samples - Wang, Hui; Lv, Yuan; Wang, Cao; Leng, Dongjing; Yan, Yan; Blessing Fasae, Moyondafoluwa; Madiha Zahra, Syeda; Jiang, Yanan; Wang, Zhiguo; Yang, Baofeng; Bai, Yunlong (Frontiers in Genetics, 2019)
Hepatocellular carcinoma (HCC) is an extremely fatal malignancy. Intestinal MicroRNAs which comes from fecal samples in humans may be involved in the pathological process of HCC.Therefore screening for functional intestinal microRNAs from fecal samples and investigating their potential role in the molecular progression of HCC are necessary. Real-time quantitative PCR (RT-PCR) has been widely used in microRNA expression studies. However, few genes have been reported as reference genes for intestinal microRNAs from fecal samples. In order to obtain more accurate intestinal microRNAs expression, we first searched for reliable reference genes for intestinal microRNAs expression normalization in quantitative RT-PCR using three softwares packages (GeNorm, NormFinder and Bestkeeper). Then we screened and predicted target genes of the differentially intestinal microRNAs of control and HCC mice through quantitative RT-PCR or miRtarBase. Finally, we also analyzed the mRNA target for enrichment of Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways by DAVID Bioinformatic Resources database .This study has successfully screened relatively suitable reference genes and we have discovered that the differential intestinal microRNAs play significant roles in the development of HCC. Top reference genes identified from this study could provide a theoretical foundation for the reasonable selection of a suitable reference gene. Furthermore, the detection of intestinal microRNAs expression that may serve as a promising therapeutic targets for the diagnosis and treatment of HCC.